"When You Take This Jump and Cross Racial Boundaries": Parents' Experiences of Raising Multiracial Children. (January 2021) - Seto, Atsuko; Becker, Kent; Lau, Jared
This qualitative study explored the lived experiences of eight parents of multiracial children. Primary themes emerged from the analysis include (a) fostering a child's multiple heritages, (b) nurturing the whole person, (c) race-conscious parenting, (d) having open communication, (e) learning on the job, and (f) a multidimensional approach to self-care. The findings revealed that parents valued open communication with their children and made efforts to not only connect them with their racial and cultural roots but also raise their children to learn about people whose cultural and racial backgrounds differ from them. Additionally, parents practiced a variety of self-care strategies to cope with stressors related to parenting and attend to their well-being.